An efficient biosensor for monitoring Alzheimer's disease risk factors: modulation and disaggregation of the Aβ aggregation process. Issue 26 (22nd May 2019) - Ma, Siyue; Qiang, Jiabao; Li, Linyang; Mo, Yan; She, Mengyao; Yang, Zheng; Liu, Ping; Zhang, Shengyong; Li, Jianli
Abstract : An efficient biosensor to monitor Alzheimer's disease risk factors and inhibit Alzheimer's disease by disaggregating Aβ aggregation. Abstract : Alzheimer's disease (AD) is a progressive neurodegenerative disease, which can lead to the complete loss of cognition. Cu 2+ and H2 S are both correlated with the physiological and pathological events of AD. Therefore, suitable methods to continuously monitor Cu 2+ and H2 S are in great demand for a better understanding of the detailed mechanism of Alzheimer's disease. Based on the heteroatom (N, O, and S) competitive effect, a series of reversible "off–on–off" fluorescent probes, S1–S3, for the detection of Cu 2+ and H2 S was designed and synthesized, which contain different alkaloids as acceptors. Their mechanism is demonstrated via IR spectroscopy, Job plot analysis and DFT calculation. These three compounds exhibited high selectivity and sensitivity (limit of detection = 1.95 nM, 1.51 nM, and 6.62 nM, respectively) for Cu 2+ with a fast response rate. In addition, S1 exhibited extremely low cytotoxicity and superb membrane permeability, which could be applied in living MCF-7 cells and living mice to monitor Cu 2+ under physiological conditions. Importantly, the excellent chelation of theS1 probe for Cu 2+ was effectively utilized to capture Cu 2+ from the aggregation of Aβ, which was observed experimentally via ThT fluorescence, transmission electron microscopy (TEM), and native polyacrylamide gel electrophoresis (native-PAGE).